T315I – a gatekeeper point mutation and its impact on the prognosis of chronic myeloid leukemia - Kaleem Bushra; Shahab Sadaf; Shamsi Tahir Sultan (Advances in Laboratory Medicine, 2024)
BCR-ABL kinase domain mutations are an important cause of resistance to tyrosine kinase inhibitors (TKIs) in chronic myeloid leukaemia (CML) of which T315I is the most treatment-resilient. This study aimed to observe the frequency of T315I and its impact on disease prognosis in terms of progression and survival.